Advances in tuberculosis diagnostics: the Xpert MTB/RIF assay and future prospects for a point-of-care test - Lawn, Stephen D; Mwaba, Peter; Bates, Matthew; Piatek, Amy; Alexander, Heather; Marais, Ben J; Cuevas, Luis E; McHugh, Timothy D; Zijenah, Lynn; Kapata, Nathan; Abubakar, Ibrahim; McNerney, Ruth; et al. (The Lancet infectious diseases, 2013)
Rapid progress has been made in the development of new diagnostic assays for tuberculosis in recent years. New technologies have been developed and assessed, and are now being implemented. The Xpert MTB/RIF assay, which enables simultaneous detection of Mycobacterium tuberculosis (MTB) and rifampicin (RIF) resistance, was endorsed by WHO in December, 2010. This assay was specifically recommended for use as the initial diagnostic test for suspected drug-resistant or HIV-associated pulmonary tuberculosis. By June, 2012, two-thirds of countries with a high tuberculosis burden and half of countries with a high multidrug-resistant tuberculosis burden had incorporated the assay into their national tuberculosis programme guidelines. Although the development of the Xpert MTB/RIF assay is undoubtedly a landmark event, clinical and programmatic effects and cost-effectiveness remain to be defined. We review the rapidly growing body of scientific literature and discuss the advantages and challenges of using the Xpert MTB/RIF assay in areas where tuberculosis is endemic. We also review other prospects within the developmental pipeline. A rapid, accurate point-of-care diagnostic test that is affordable and can be readily implemented is urgently needed. Investment in the tuberculosis diagnostics pipeline should remain a major priority for funders and researchers.